Perilaku Konsumen Gen Z Dalam Mengkonsumsi Produk Minuman Mixue Viral Harga Murah - Pika, Putu Ayu Titha Paramita; Sari, Desak Made Febri Purnama; Parasari, Nyoman Sri Manik (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the behavior of Generation Z consumers in consuming viral drink products, particularly Mixue, known for its affordability. The methodology employed in this research is a phenomenological approach, allowing for a deep understanding of consumers' subjective experiences and how these influence their purchasing decisions. Data were collected through in-depth interviews, observations, and documentation from various informants who belong to Generation Z. The findings indicate that consumers' purchasing decisions are influenced by three main factors based on the Theory of Planned Behavior: behavioral control, subjective norms, and attitudes toward behavior. Consumers tend to consider perceptions of reasonable costs and high product quality. Moreover, the influence of social media and recommendations from friends proved to be significant in motivating consumers to try Mixue. The social experiences associated with shopping, often involving interactions with peers, are believed to enhance satisfaction and brand loyalty. These findings provide crucial insights for business practitioners in formulating more effective and sustainable marketing strategies, particularly in reaching young consumers in the digital age